Pulmonary arteriovenous malformations: diagnosis - Saboo, Sachin S. (Cardiovasc Diagn Ther, 2018)
Pulmonary arteriovenous malformations (PAVMs) are rare, abnormal low resistance vascular structures that connect a pulmonary artery to a pulmonary vein, thereby bypassing the normal pulmonary capillary bed and resulting in an intrapulmonary right-to-left shunt. The spectrum of PAVMs extends from microscopic lesions causing profound hypoxemia and ground glass appearance on computed tomography (CT) but with normal catheter angiographic findings to classic pulmonary aneurysmal connections that abnormally connect pulmonary veins and arteries. These malformations most commonly are seen in hereditary hemorrhagic telangiectasia (HHT). They are rarely due to secondary conditions such as post congenital heart disease surgery or hepatopulmonary syndrome (HPS). The main complications of PAVM result from intrapulmonary shunt and include stroke, brain abscess, and hypoxemia. Local pulmonary complications include PAVM rupture leading to life-threatening hemoptysis or hemothorax. The preferred screening test for PAVM is transthoracic contrast echocardiography (TTCE). CT has become the gold standard imaging test to establish the presence of PAVM. Endovascular occlusion of the feeding artery is the treatment of choice. Collateralization and recanalization of PAVM following treatment may occur, and hence long term clinical and imaging follow-up is required to assess PAVM enlargement and PAVM reperfusion.